x+6+12x-7=

Simple and best practice solution for x+6+12x-7= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+6+12x-7= equation:


Simplifying
x + 6 + 12x + -7 = 0

Reorder the terms:
6 + -7 + x + 12x = 0

Combine like terms: 6 + -7 = -1
-1 + x + 12x = 0

Combine like terms: x + 12x = 13x
-1 + 13x = 0

Solving
-1 + 13x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 13x = 0 + 1

Combine like terms: -1 + 1 = 0
0 + 13x = 0 + 1
13x = 0 + 1

Combine like terms: 0 + 1 = 1
13x = 1

Divide each side by '13'.
x = 0.07692307692

Simplifying
x = 0.07692307692

See similar equations:

| -x/4+7=5 | | 9x+17+5=90 | | 12-6/3 | | 5b-18+6b=-7 | | y-7=-3/4x-15/4 | | 4/8r-150=230 | | n/9=69 | | n/9= | | x=log(3)(8) | | m^2=7m+6 | | 1/2x+3=-4 | | 7(1-8x)-1=-3(5x-2) | | 5(6+6x)=150 | | 2[(8x+2)+6]=5(7x+4) | | C/-10+26=46 | | (5.9p+.3p)+7.1=-2.2 | | y/2+4=-18 | | 7+7x=x+73 | | 5(x-3)=-5(3-x) | | 5x+3x=3x*3 | | y^5=19 | | 26y+11=29-29y+29y | | -3t*6=0 | | 3x-y=5y | | 3x(3x)=12 | | -3-11(-9x+8)=-7(7x-10)+3x-10x | | 5x^2-4x-7= | | 7.2+g=9.1 | | 1.5x-4=.6x+6 | | -450/-9 | | y+2=7/8(x-3) | | 3x-5(x-5)=-7+4x-10 |

Equations solver categories